(untitled) (Research, Society and Development, 2020)
This research seeks to identify if the exchange rate and price of the beef cattle has a relation, that is, to identify if both have a dynamics in the market. The methodology used has a quantitative approach. The cointegration tests of Engle Granger and Johansen were used to verify if the variables have a long term equilibrium. The results showed that there is a long-term relationship between the price of the bullock and the exchange rate. The markets for bullion and the exchange rate are interconnected, as the results of the cointegration tests showed. Long-term exchange rate shocks influence the increase in the price of the bullock. The bullock is a commodity and one of the main products of the Brazilian exporting list. Thus, it can be considered that, in times of greater external uncertainty, the price of the beef cattle adjusts with greater speed to avoid unexpected losses to the producers.